SN 2016ije: An SN 2002es-like Type Ia Supernova Exploded in a Metal-poor and Low-surface Brightness Galaxy - Zhitong Li; Tianmeng Zhang; Xiaofeng Wang; Jujia Zhang; Lluís Galbany; Alexei V. Filippenko; Thomas G. Brink; Chris Ashall; WeiKang Zheng; Thomas de Jaeger; Fabio Ragosta; Maxime Deckers; et al. (The Astrophysical Journal, 2023)
We have conducted photometric and spectroscopic observations of the peculiar Type Ia supernova (SN Ia) 2016ije that was discovered through the Tsinghua-NAOC Transient Survey. This peculiar object exploded in the outskirts of a metal-poor, low-surface brightness galaxy (i.e., M _g = −14.5 mag). Our photometric analysis reveals that SN 2016ije is subluminous ( ${M}_{B,\max }$ = −17.65 ± 0.06 mag) but exhibits relatively broad light curves (Δ m _15 ( B ) = 1.35 ± 0.14 mag), similar to the behavior of SN 2002es. Our analysis of the bolometric light curve indicates that only 0.14 ± 0.04 M _⊙ of ^56 Ni was synthesized in the explosion of SN 2016ije, which suggests a less energetic thermonuclear explosion when compared to normal SNe Ia, and this left a considerable amount of unburned materials in the ejecta. Spectroscopically, SN 2016ije resembles other SN 2002es-like SNe Ia, except that the ejecta velocity inferred from its carbon absorption line (∼4500 km s ^−1 ) is much lower than that from silicon lines (∼8300 km s ^−1 ) at around the maximum light. Additionally, most of the absorption lines are broader than other 02es-like SNe Ia. These peculiarities suggest the presence of significant unburned carbon in the inner region and a wide line-forming region along the line of sight. These characteristics suggest that SN 2016ije might originate from the violent merger of a white dwarf binary system, when viewed near an orientation along the iron-group-element cavity caused by the companion star.